2019
DOI: 10.1080/15476286.2019.1643100
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleotide polymorphism rs13079080 is associated with differential regulation of the succinate receptor 1 (SUCNR1) gene by miRNA-4470

Abstract: Oxidative stress is a feature of many common diseases. It leads to excessive formation and subsequent release of the mitochondrial metabolite succinate, which acts as a signalling molecule through binding the succinate receptor (SUCNR1). Recently, a potential role for SUCNR1 was proposed in age-related macular degeneration (AMD), a common cause of vision loss in the elderly associated with increased oxidative stress. Here, we evaluated the potential effect of genetic variants in SUCNR1 on its expression throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 32 publications
1
3
0
Order By: Relevance
“…A genome-wide association study (GWAS) using over 16,000 AMD patients and 17,000 controls have linked AMD to several genes involved in lipid metabolism and the complement system 25 . Favret et al described several genetic variants in the SUCNR1 gene to be associated with dry AMD 17 and in a recent study we also identified a genetic variant in the SUCNR1 gene to be associated with AMD 18 . Furthermore, we showed a possible mechanism of SUCNR1 mRNA downregulation as a result of this variant.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…A genome-wide association study (GWAS) using over 16,000 AMD patients and 17,000 controls have linked AMD to several genes involved in lipid metabolism and the complement system 25 . Favret et al described several genetic variants in the SUCNR1 gene to be associated with dry AMD 17 and in a recent study we also identified a genetic variant in the SUCNR1 gene to be associated with AMD 18 . Furthermore, we showed a possible mechanism of SUCNR1 mRNA downregulation as a result of this variant.…”
Section: Discussionsupporting
confidence: 56%
“…It was shown that deficiency of Sucnr1 in mice led to outer retinal lesions and accumulation of oxidative LDL (oxLDL), a lipid-protein complex found in drusen. Moreover, we recently described a single nucleotide polymorphism in the 3'-UTR of the SUCNR1 gene, which is enriched in the EUGENDA AMD cohort, and reduces the SUCNR1 expression levels in vitro 18 .…”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the role of SUCNR1 in AML has not yet been explored. SUCNR1 is a sensor of oxidative stress, which may assist in the cells ability to sense and manage excessive oxidative stress (27). In this regard, succinate is considered an oncometabolite, which promotes tumorigenesis by promoting angiogenesis in experimental models as well as a transgenic zebrafish cancer model (28).…”
Section: Discussionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a kind of short non-coding RNA molecule (∼22 nucleotides; nt) that suppress gene expression post-transcriptionally by binding to the 3ʹ-UTR region to mediate mRNA degradation or translational repression ( Li et al, 2018 ; Bofill-De Ros et al, 2019 ; Louer et al, 2019 ). It has been estimated that nearly all mRNA transcripts contain miRNA response elements (MREs), and more than 60% of human genes have been identified as regulated by miRNA ( Friedman et al, 2009 ; Zhang et al, 2019a ).…”
Section: Introductionmentioning
confidence: 99%